Unlocking the hidden potential of Mexican teosinte seeds: revealing plant growth-promoting bacterial and fungal biocontrol agents - De-la-Vega-Camarillo, Esaú; Hernández-García, Juan Alfredo; Villa-Tanaca, Lourdes; Hernández-Rodríguez, César (Frontiers in Plant Science, 2023)
The bacterial component of plant holobiont maintains valuable interactions that contribute to plants' growth, adaptation, stress tolerance, and antagonism to some phytopathogens. Teosinte is the grass plant recognized as the progenitor of modern maize, domesticated by pre-Hispanic civilizations around 9,000 years ago. Three teosinte species are recognized: Zea diploperennis, Zea perennis, and Zea mays.In this work, the bacterial diversity of three species of Mexican teosinte seeds was explored by massive sequencing of 16S rRNA amplicons.